Entrepreneurial Competencies of Indian Women Entrepreneurs in Micro Service Enterprises - Mahajan, Ashish; Chowdhary, Rupal (AMC Indian Journal of Entrepreneurship, 2022)
Research in entrepreneurship domain has proved positive association of entrepreneurial competencies with the performance of business enterprises. These competencies have been reported differently by men and women entrepreneurs. This study was an attempt to shift the focus from traditional challenges to the growth vision of women entrepreneurs which can be achieved through understanding and enhancing entrepreneurial competencies relevant to business enterprise. This study reflected the entrepreneurial competencies of women entrepreneurs from India through a well designed questionnaire listing the psychometric statements that indicate the competencies of respondents. Responses from 157 emerging women entrepreneurs running micro service business units from Indian urban areas revealed fresh insight in this domain. Results of the study indicated the emergence of new profiles of women entrepreneurs in the service sector. Factor analysis revealed three clusters of entrepreneurial competencies namely, personal and human relations competency, core entrepreneurial competency, business and management competency which showed that women as entrepreneurs are good at personal and behavior competencies. This differentiates them from their male counterparts when compared with past researches. This study aimed at providing agenda for training and development of evolving breed of women entrepreneurs through understanding the required entrepreneurial competencies. The study contributes to the next level in women entrepreneurship literature in developing countries like India.